Dihydroauroglaucin Isolated from the Mediterranean Sponge Grantia compressa Endophyte Marine Fungus Eurotium chevalieri Inhibits Migration of Human Neuroblastoma Cells - Marzia Vasarri; Giovanni Andrea Vitale; Giovanna Cristina Varese; Emanuela Barletta; Maria Valeria D'Auria; Donatella de Pascale; Donatella Degl'Innocenti (MDPI AG, 2022)
Cancer cell migration is a hallmark of the aggressiveness and progression of malignancies such as high-risk neuroblastoma. Given the lack of effective therapeutic solutions to counteract cancer progression, basic research aims to identify novel bioactive molecules with inhibitory potential on cancer cell migration. In this context, this work investigated the role of members of the salicylaldehyde secondary metabolite set from the sponge endophyte fungus Eurotium chevalieri MUT 2316 as potential inhibitors of human neuroblastoma SH-SY5Y cell migration. Since tetrahydroauroglaucin (TAG) and dihydroauroglaucin (DAG) were isolated in large amounts, both were evaluated for their anticancer properties towards SH-SY5Y cells. Both molecules were found to be non-cytotoxic by MTT assay and cytofluorimetric analysis. Moreover, DAG showed efficacy in inhibiting the highly migratory phenotype of SH-SY5Y cells by wound healing assay; whereas TAG, although structurally similar to DAG, showed no anti-migratory effect. Therefore, this work provides good reasons to conduct further in vitro and in vivo studies focusing on DAG as a potentially useful migrastatic natural marine molecule.